2021
DOI: 10.1021/acsami.0c16846
|View full text |Cite
|
Sign up to set email alerts
|

Physically Unclonable Surfaces via Dewetting of Polymer Thin Films

Abstract: From anti-counterfeiting to biotechnology applications, there is a strong demand for encoded surfaces with multiple security layers that are prepared by stochastic processes and are adaptable to deterministic fabrication approaches. Here, we present dewetting instabilities in nanoscopic (thickness <100 nm) polymer films as a form of physically unclonable function (PUF). The inherent randomness involved in the dewetting process presents a highly suitable platform for fabricating unclonable surfaces. The thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 58 publications
0
75
1
Order By: Relevance
“…Although we have initially performed this annealing in an inert atmosphere, our later experiments (vide infra) have demonstrated that the ambient atmosphere annealing is also possible, thanks to the good thermal stability and the robust chemical structure of 2EHO-TPA-CNPE. While heating above glass transition at relatively high temperatures (>200-250 °C) was typically required for the formation of dewetted structures in polymer thin films, [53,55,56] the dewetting dynamics are quite different in the case of nanoscopic molecular thin-films. The solid-state of molecular semiconductor thin-films, from the cumulative cohesive energetics perspective, are bound by relatively weak π-interactions and van der Waals forces, especially when compared with polymeric materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we have initially performed this annealing in an inert atmosphere, our later experiments (vide infra) have demonstrated that the ambient atmosphere annealing is also possible, thanks to the good thermal stability and the robust chemical structure of 2EHO-TPA-CNPE. While heating above glass transition at relatively high temperatures (>200-250 °C) was typically required for the formation of dewetted structures in polymer thin films, [53,55,56] the dewetting dynamics are quite different in the case of nanoscopic molecular thin-films. The solid-state of molecular semiconductor thin-films, from the cumulative cohesive energetics perspective, are bound by relatively weak π-interactions and van der Waals forces, especially when compared with polymeric materials.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, one would think that the relatively high surface energy (contact angle ≈ 95° and γ ≈ 41.1 mJ m −2 ) of the end‐grafted PS layer is the main thermodynamic driving force for the observed dewetting process, as we have recently seen in polymer films. [ 53 ] Thanks to the great structural mobility, flexible alkyl chains, and amorphous microstructure of the current small molecule, perfect dewetting with randomly positioned features was formed also on a freshly cleaned silicon substrate (contact angle ≈ 0° showing a high surface energy) (Figure 5b). In this case, the thermal annealing was performed in the ambient atmosphere at the same temperature (170 °C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any random physical process is a potential candidate for the realization of PUFs. Indeed, there is already a plethora of research accounts 12 19 that include exotic solutions like aerogels 20 , Raman tags 21 , plasmonic nanopapers 22 wrinkles on glasses 23 , perovskite fluorescent dots 24 or even edible unclonable functions 25 to name a few. The PUF scenery in the literature is evolving fast necessitating taxonomy activities like the one presented by McGrath and co authors 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The evaporation, most of the time of part of the external phase, may provoke instabilities 7 . For example, dewetting may appear due to differential evaporation of the solvents [8][9][10][11] . Other capillary phenomena may cause convection that structures the film [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%